Direct adsorption sampling and ambient mass spectrometry analysis of tobacco smoke with porous paper strips - Yang, Ji; Xiong, Wen; Liu, Chunbo; Li, Juan; Zhu, Ruizhi; Xia, Jianjun; Yin, Zhijiang; Tian, Ran; Tang, Shiyun; Li, Zhenjie; Li, Hui; Han, Ying; et al. (Frontiers in Chemistry, 2022)
Chemical analysis of atmospheric aerosols by conventional analytical methods is usually required to perform complicated and time-consuming sample preparation processes. In recent decades, ambient ionization mass spectrometry (AI-MS) methods have been proven to be simple, rapid, and effective analytical tools for direct analysis of various complex samples. In this work, we applied porous paper filters for direct adsorptive sampling of tobacco smoke, and then the sampled paper filters were performed the emitters of the paper spray ionization (PSI) device. An auto-sampling device was made to control the generation and collection of tobacco smoke. Nicotine, the typical compound of tobacco smoke, was used to optimize the key conditions of auto-sampling. Moreover, different types of tobacco smoke were also compared with multivariate variable analysis, and the makers of tobacco smoke from different sources of tobacco smoke were investigated. By using this method, direct sampling and analysis of a single tobacco sample can be completed within minutes. Overall, our results show that PSI-MS is a powerful tool that integrates collection, extraction, ionization, and identification analytes in smoke.